RESPONSE TO "REKTANIGAMA": A WEBSITE BASED FARMING RECORD APPLICATION - Nurhayati, Azizatun; Widada, Arif Wahyu; Irham, Irham; Anantasari, Esti; Devi, Laksmi Y.; Subejo, Subejo (AGRIBEST, 2020)
Comprehensive farm recording, not only recording the inputs used in farming, but also scheduling activities carried out in the process of cultivation. Farming records are important to be owned by farmers as a basis for decision making. Unfortunately, some farmers do not have adequate farming records. In organic farming, farm record is also one of the things required for organic certification. This study aims to determine the response of stakeholders and farmers to Rektanigama, a website-based farm recording application.The number of participant in this research are 27 respondents of stakeholders and 21 respondents of farmers. The research was conducted by census method and focus group discussion  The results showed that stakeholders and farmers considered Rektanigama to be sufficiently good and could be applied as a farm recording tool. Total score for Rektanigama according to farmers was 7.80 and 6.88 according to stakeholders, respectively. In addition, farmers already know the importance of recording farming but have not implemented it. Stakeholders and farmers provide advice that the Rektanigama be disseminated massively to be able to support the needs of farming records, especially for farmers who need organic certification.